Risk management in the venture capital industry: Managing risk in portfolio companies - Dorian Proksch; Wiebke Stranz; Andreas Pinkwart; Michael Schefczyk (The Journal of Entrepreneurial Finance (JEF), 2016)
Managing risk is one of the main activities of venture capital companies. Despite the fact that this topic is of high practical relevance, only little research was published on risk management performed by venture capital companies in their ventures. Hence, we conducted a structured literature review which was the basis for developing five hypotheses concerning measures to decrease failure risk in venture capital-backed ventures. We tested these hypotheses with an empirical data set of 93 venture capital-backed ventures in Germany using original deal data from nine different venture capital funds using a structural equation model. We showed that the experience and the skills of the corresponding investment manager have a significant negative impact on the failure risk of a venture. Investment manager's experience and skills were measured by the working and founding experience, the technology expertise and the network size. Hence, the results emphasize the importance of the selection of the investment manager for risk management in venture capital investments.
Keywords: G32; G24; L26; M13; 650; risk management; failure risk; venture capital; new-technology-based firms